(untitled) (Medicine Today, 2026)
Introduction with Objective: Tibial shaft fractures are the most prevalent type of tibia fracture. Intramedullary nailing is the standard procedure for surgical treatment of displaced tibial shaft fractures. Tibial nail insertion with suprapatellar approach with the knee in semi extended position which has advantage over infrapatellar approach. The aim of this study is to compare the surgical and clinical outcome of suprapatellar and infrapatellar approach for the tibial intramedullary nailing in patient with tibial shaft fractures. Methods: This Prospective Study was carried out among 48 patients attending at the department of Orthopedics Surgery at Chittagong Medical College Hospital; Chittagong for the treatment tibial fracture within the defined period from May 2022 to April 2023. Total 4 patients were dropped out in the middle of follow up. So follow up was done among 44 patients. All the data were compiled and sorted properly and the quantitative data was analyzed statistically by using Statistical Package for Social Science. Results: Twenty two patients in each group completed the study per protocol and included in the analysis. Both groups are comparable in terms of their age, fracture type and fracture location (P>0.05) .The average time of union was 3.52±0.898 months and 3.36±0.790 months respectively in suprapatellar and infrapatellar approach group (P=0.535). The average duration of operation was 90.04±8.035 and 76.46±9.060 minutes respectively in suprapatellar and infrapatellar approach group (P<0.001). Mean ± SD fsluroscopy time in suprapatellar approach was 115.58 ± 8.387 seconds and in infrapatellar approach was 105.38±9.102 (P<0.001). There was no significant difference among the two groups of nailing according P Value regarding complication like malalignment. Average ROM in suprapatellar approach group was 130.91±1.5 and in infrapatellar approach group was 125.38±1.88 (P<0.001). Suprapatellar approach shows significantly better outcome by mean Lysholm Knee score in comparison to infrapatellar approach according (P Value). The proportion of patients achieved excellent functional outcome was 18(81.8%) and 17(77.3%) in suprapatellar and infrapatellar approach group (P=0.892). Conclusion: It can be concluded that suprapatellar approach produced better functional outcome than infrapatellar approach in the treatment of tibial shaft fracture when considering mean lysholm knee score, range of motion and rate of malalignment in this present clinical trial. Medicine Today 2026, Vol.38 (1): 56-59